Multiple poles resonances coupling with high sensitivity sensing for multiple bulging black phosphorus-based metasurface - Nengxun Yang; Yixuan Wang; Lingqiao Li; Yang Ren; Zhihui He; Wei Cui; Zhimin Yang; Shaojun Lu; Xiongxiong Wu; Lang Bai (New Journal of Physics, 2023)
Herein, a multiple bulging black phosphorus (BP)-based metasurface is proposed for studying its reflection responses and sensing performances through the finite-difference time-domain simulation method. It is shown that, the reflection dips are caused by the coupling between dipole resonance modes and poly-poles resonance modes. Moreover, the dipoles resonance modes and poly-poles resonance modes can mutually enhance and inhibit each other, and tunable reflection spectra can be realized by symmetrically and asymmetrically adjusting the bulging of the proposed BP-based metasurface. In addition, the reflection spectra as a function of the polarization of incident light are discussed. We can find that a dipole resonance mode on the vertical side at the direction of ZZ for BP is gradually fully excited, resulting in an additional obvious reflection dip as the polarization angle θ increases from 0° to 90°. Especially, the sensing performance with the maximum of sensitivity S = 1.5 μ m/RIU can be realized in the proposed BP-based metasurface. The results may provide a way to design micro-nano plasmonic devices.